Analisis Wacana Kritis Fairclough terhadap Berita Aplikasi PeduliLindungi - Nurnaningsih Nurnaningsih (Universitas Sarjanawiyata Tamansiswa, 2022)
The spread of COVID-19 sufferers has inspired the government to create an application to protect and care. Meanwhile, the purpose of this research is to describe the news about the care-protect application in 4 news articles uploaded by the CNN Indonesia news site based on the three-dimensional Fairclough model. The research method used is descriptive qualitative. The data collection technique used is the bibliography collection method, with the research source being the CNN Indonesia online news page, while the data is in the CNN Indonesia news page. Data analysis technique is to use Miles and Huberman. Critical Discourse Analysis on CNN Indonesia news on the care to protect application is as follows. This CNN Indonesia news is more inclined to the government with the aim of socializing the application of protecting and caring for the community. This is done by the government to reduce the rate of COVID-19 in Indonesia. The CNN Indonesia news that contained the Pedulilindungi application seemed to urge and inform the ways in which the application was implemented. Actually the news does not appeal but tends to force it because in some articles there is the word mandatory. This government coercion is subtly so that people are willing to vaccinate against covid 19 and the government can better control the rate of people who are exposed or have become covid survivors. Keywords: News, PeduliLindungi Application, Critical Discourse Analysis